Vitamina D e Inflamação na Leishmaniose Visceral - Gustavo Gomes de Oliveira (2023)
Activated vitamin D (VitD) has several functions in the body that go far beyond its role in the homeostasis of calcium and phosphorus minerals. The action of this hormone on the immune system has been widely explored in recent decades, revealing its relationship with infectious, parasitic and autoimmune diseases. Low levels of VitD were observed in dogs infected with visceral leishmaniasis (VL), demonstrating a relationship with the severity of the disease. However, it has not been established whether there is a relationship between hypovitaminosis D and inflammatory markers in these animals. Therefore, the objective of this project is to verify the relationship between inflammation in dogs with VL and changes in VitD levels. For this, 23 dogs were used, eight healthy for the control group (CG) and 15 positives for VL in parasitological or serological tests, without showing azotemia to form the sick group (SG). VitD, creatinine, albumin, C-reactive protein and hemoglobin levels were measured and compared between groups using the Mann-Whitney test. Correlations between vitamin D and albumin, C-reactive protein and hemoglobin were performed using the Spearman test. The significance level used was 0.05. All inflammatory markers showed statistical difference in their concentrations in the studied groups. The SG had a higher prevalence of vitamin D deficiency (46%) when compared to the CG (0%). Moderate correlation was observed between vitamin D and C-reactive protein (rs:-0.48; p:0.03). All animals with vitamin D deficiency had hypoalbuminemia. Inflammation is related to vitamin D deficiency, which can lead to a cycle of inflammation and hypovitaminosis D, aggravating the patient's condition.